2016
DOI: 10.1016/j.joco.2016.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Corneal biomechanics after small-incision lenticule extraction versus Q-value–guided femtosecond laser-assisted in situ keratomileusis

Abstract: PurposeThe aim of this study was to compare the changes in corneal biomechanical properties following small-incision lenticule extraction (SMILE) versus Q-value–guided femtosecond laser-assisted in situ keratomileusis (Q-FS-LASIK).MethodsIn this prospective comparative study, patients with a sphere plus cylinder measurement of less than −10.00 D and cylinder measurement of less than −5.00 D were included in the study. A total of 160 patients (160 eyes) with myopia and myopic astigmatism were divided into the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…There were several clinical studies on biomechanical changes in the cornea after LASIK and SMILE. [3][4][5][6][7][8][9][10] A few reported similar biomechanical changes in the cornea after femtosecond LASIK and SMILE. [3][4][5][6] Other studies reported better biomechanical outcomes in SMILE eyes than in LASIK eyes.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…There were several clinical studies on biomechanical changes in the cornea after LASIK and SMILE. [3][4][5][6][7][8][9][10] A few reported similar biomechanical changes in the cornea after femtosecond LASIK and SMILE. [3][4][5][6] Other studies reported better biomechanical outcomes in SMILE eyes than in LASIK eyes.…”
mentioning
confidence: 92%
“…[3][4][5][6][7][8][9][10] A few reported similar biomechanical changes in the cornea after femtosecond LASIK and SMILE. [3][4][5][6] Other studies reported better biomechanical outcomes in SMILE eyes than in LASIK eyes. [7][8][9][10] Similarly, corneal tissue healing and Scheimpflug densitometry changes indicated a moderately better response in SMILE eyes.…”
mentioning
confidence: 92%
“…Many researchers have compared the postoperative CH and CRF between the SMILE and FS-LASIK groups. Two reports by Zhang Jun et al [13,14] showed no significant postoperative differences in CH and CRF between the SMILE group and the FS-LASIK group. However, Wenjing WU et al [15] and Elmohamady et al [16] found that CH and CRF both exhibited postoperative differences between the SMILE group and the FS-LASIK group.…”
Section: Discussionmentioning
confidence: 84%
“…The studies by Wu & Wang () and Zhang et al. () did also not state the comparisons of CH and CRF between the groups preoperative or postoperative, which make the interpretation of results uncertain, especially the finding of a statistically significant difference as described by Wu & Wang (). Likewise, Wang et al.…”
Section: Resultsmentioning
confidence: 97%
“…The study by Zhang et al. () did not report the mean age or age range for inclusion and was the only nonrandomised study, which did not find statistical significant differences in the corneal biomechanical changes between the groups.…”
Section: Resultsmentioning
confidence: 99%